La prescripción extraordinaria adquisitiva de dominio de la cuota de un copropietario. - Haro Betún, Daniel Israel (2022)
In developing this topic, each of the edges that derive from it has been framed; therefore, we will discuss domain, possession, and co-ownership as starting points toward a deeper analysis of the extraordinary acquisitive prescription of the domain. From the doctrinal analysis carried out, two positions could be identified; the first thesis says that it is not possible for the extraordinary prescription of the dominion of the quota of a co-owner, whose main foundation is when a co-ownership is constituted, it is not posible to enjoy an exclusive possession. In contrast to this thesis, we find the one that admits such prescription of the quota of a co-owner proceeds because one of the co-owners ignores the right of the other co-owners and starts to enjoy the property with the spirit of lord and owner, together with the peaceful, continuous and uninterrupted manner at the time of possessing the property, in addition to complying with the time stipulated in the law. Within the research project, we will analyze these theses. Then we will go into the local regulations, determining which of these positions is the closest to the legal reality of our country.